CFD Analysis of Motorcycle Moving on Bridge During Overtaking Under Crosswind Conditions - Tiong Woei Ting; Ishak, Izuan Amin; Mohammad Arafat; Nofrizalidris Darlis; Nur Haziqah Shaharuddin; Ahmad Faiz Mohammad (International Journal of Integrated Engineering, 2026)
This study examines the aerodynamic challenges faced by motorcycles during overtaking maneuvers on bridges under crosswind conditions, addressing a critical safety issue often overlooked in existing research, which primarily focuses on cars. With over 20,000 motorcyclists traversing the Penang Bridge daily and exposed to crosswinds reaching 18.5 km/h, the risks of accidents due to aerodynamic instability are significant. Using Computational Fluid Dynamics (CFD) simulations through ANSYS Fluent, this research analyzes the aerodynamic interactions between motorcycles and overtaking vehicles under crosswind angles of 20°, 30°, 40°, and 50°. A grid-independent approach ensures accuracy in evaluating key aerodynamic parameters, including drag, lift, and side force coefficients, during different phases of overtaking maneuvers. The results reveal that crosswinds at a yaw angle of 50° increase the drag coefficient by 45% and the side force coefficient by 72% compared to baseline conditions without crosswind. These amplified aerodynamic loads substantially heighten the risk to rider stability. Conversely, the presence of an overtaking vehicle reduces drag force on the motorcycle by up to 20% due to partial shielding but introduces wake turbulence that affects lateral stability. Pressure distribution analysis shows a high-pressure concentration on the windward side, contributing significantly to lateral forces that destabilize the motorcycle. These findings offer critical insights into the behavior of motorcycles under challenging environmental conditions, emphasizing the need for enhanced bridge safety guidelines, optimized motorcycle designs, and improved rider safety strategies. This research provides a foundation for future studies on mitigating aerodynamic instability and reducing accident risks, contributing to safer motorcycle operations in crosswind-prone environments.